What Does Leadership Look Like in Child and Youth Care Practice: A Course-based Qualitative Inquiry - Bellefeuille, Gerard (Advances in Social Sciences Research Journal, 2021)
The aim of this course-based research is to explore how child and youth care (CYC) students understand the concept of leadership within the context of CYC practice. Data was collected through online interviews and an arts-based activity. From the data analysis, four main themes were extracted: leadership as relational process, leadership as authenticity, leadership as complexity, and leadership as praxis. The findings reveal that CYC students characterize CYC leadership as a way of being relationally engaged with others that is more a way of being in the world than a matter of what one knows or does.